Hubungan Deprivasi Kolektif Dan Agresivitas - Rumandjo, Karolin Rista (Persona:Jurnal Psikologi Indonesia, 2015)
This study aims to prove empirically the relationship of collective deprivation and aggressiveness. Variables that will be examined in this study is composed of the independent variable (X), namely collective deprivation and dependent variable (Y) is aggressiveness. The hypothesis in this study, is "There is a positive relationship between collective deprivation with aggressiveness". The data in this study will be analyzed by using Product Moment run the SPS program. Results of the analysis showed that the correlation coefficient of 0.094 at p equal to 0.646 (p>0.05) means that there is no relationship between collective deprivation with aggressiveness, in other words there is no relationship between collective deprivation with aggressiveness, so that this hypothesis was rejected. The results of the Z-test to collective deprivation z values obtained for 5807 at p 0.000 (p<0.01), then the average - average collective deprivation on respondents showed the presence of high deprivation, but the Z-test results values obtained against the aggressiveness of - 17 388 at p 0.000 (p<0.01) that shows that the subjects in this study were relatively low aggressiveness